2015
DOI: 10.1002/prca.201500090
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics as an innovative tool to investigate frontotemporal disorders

Abstract: Neurodegenerative diseases are characterized by slow progressive loss of one or more functions of the CNS. Worldwide, the number of people affected by neurodegeneration is dramatically high and the social impact is upsetting. While being a heterogeneous group of diseases, most of these pathologies manifest similar clinical features and illness progression, thus making their diagnosis elusive. With its ability to meet the needs of neurodegenerative research, proteomics could help facilitate the diagnosis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…A comprehensive analysis of the Hela cell proteome by SILAC 2DE‐LC‐LTQ OrbiTrap XL revealed that 676 spots from 816 analyzed ones contained at least two with up to 22 different proteins . Combined with 2DE gel image analysis, conventional 2DE‐based comparative proteomics has been extensively used to determine “differentially expressed proteins” under different physiological, pathological, or pathophysiological conditions as reviewed in the selected publications . However, the protein composition in a human tissue, cell, or body‐fluid proteome is very complex with a very wide abundance range and complicated huge protein speciation caused by splicing, truncation and modification .…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis of the Hela cell proteome by SILAC 2DE‐LC‐LTQ OrbiTrap XL revealed that 676 spots from 816 analyzed ones contained at least two with up to 22 different proteins . Combined with 2DE gel image analysis, conventional 2DE‐based comparative proteomics has been extensively used to determine “differentially expressed proteins” under different physiological, pathological, or pathophysiological conditions as reviewed in the selected publications . However, the protein composition in a human tissue, cell, or body‐fluid proteome is very complex with a very wide abundance range and complicated huge protein speciation caused by splicing, truncation and modification .…”
Section: Introductionmentioning
confidence: 99%
“…7 Most studies on fluid biomarkers in FTD have used targeted approaches, allowing measurement of known protein candidates only, 7,8 while unbiased approaches have scarcely been performed. 9,10 In autosomal dominant Alzheimer's disease, unbiased approaches have uncovered early changes in the proteome. 11 In the present study, we investigated CSF proteomics by unbiased mass spectrometry (MS) in presymptomatic and symptomatic GRN mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The more recently applied endophenotype based data correlation approach appears to be more reliable [16]. However, limited proteomic studies are available for FTD (for review see [21][22][23][24][25]). For example, Hu and co-workers identified 151 differentially regulated proteins for FTD, but these only yielded 78% specificity for FTD with TDP-43 pathology (FTD-TDP) over FTD with tau pathology (FTD-tau) [26].…”
Section: Introductionmentioning
confidence: 99%